2021
DOI: 10.1016/j.jbc.2021.101179
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lysine restriction induces lipid accumulation in skeletal muscle through an increase in serum threonine levels in rats

Abstract: Dietary lysine restriction induces lipid accumulation in skeletal muscle through an increase in serum threonine levels in rats,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…It is worth mentioning that, unlike the decrease in levels seen with the majority of amino acids, histidine and serine increased by about 50 % and threonine by 2·5-fold with the deficient diet. The increase in threonine levels (and at a lower extent in histidine and serine) in lysine deficiency was previously reported in the literature ( 53 57 ) and could be explained by a hindered utilisation and/or oxidation of these amino acids.…”
Section: Discussionsupporting
confidence: 65%
“…It is worth mentioning that, unlike the decrease in levels seen with the majority of amino acids, histidine and serine increased by about 50 % and threonine by 2·5-fold with the deficient diet. The increase in threonine levels (and at a lower extent in histidine and serine) in lysine deficiency was previously reported in the literature ( 53 57 ) and could be explained by a hindered utilisation and/or oxidation of these amino acids.…”
Section: Discussionsupporting
confidence: 65%
“…Several studies have previously evaluated the potential effects of lysine on the regulation of lipid metabolism in animals. Goda et al [ 9 ] reported that triglycerides accumulate more in the muscle of rats fed with dietary lysine restriction. Katsuma et al [ 20 ] conveyed that a lysine-deficient diet can increase the lipid content in the skeletal muscle of pigs.…”
Section: Resultsmentioning
confidence: 99%
“…Lysine is a promising amino acid. Although reports are inconsistent, amino acids are reported to induce lipid accumulation in vivo and in vitro [ 9 , 10 ]. The mechanisms involved in enhancing adipocyte differentiation through decreasing level of lysine are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the abnormal levels of D-homocysteine, the L-aspartic acid, and L-homoserine indicate a disordered cysteine and methionine metabolism, which plays a role in vascular inflammation, liver disease, and chronic renal failure [ 37 ]. Additionally, an elevated L-threonine level is associated with an abnormal muscular lipid accumulation [ 38 ]. Here, the LRA intake mitigated the impacts of the DG on these metabolites and may reduce the risk of age-related hepatic, renal, cardiovascular, and cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 99%